Agama dan Pendidikan dalam Pencegahan Terorisme - Nurdin, Nurdin (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2013)
The active role of education is considered vital as overall protection for the prevention of early symptoms and understand violence in the name of religion, especially religious education should be considered. Religious teachings that teach tolerance, politeness, friendliness, hate vandalism, and advocating unity not often echoed. Educational rhetoric presented to the community more often pitched mock rather than invite, hit more often than embracing, more often than educating scolded. Therefore, the values ofreligion and religious education should be prioritized to reduce a variety of radical thought.